Educação Profissional e Tecnológica: Cotejamentos Entre Brasil e Argentina na Busca do “Novo Desenvolvimentismo” - Remi Castioni (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2020)
This article is the result of the dialogue between our researches, which analyze models and structures of professional and technological education in contemporary times. In the present article we have chosen the trajectories of Brazil and Argentina, particularly in the last decade, when governments assume development strategies with the State as the main actor, connecting with the Economic Commission for Latin America and the Caribbean – Eclac – strategy in the years 1950/60, facing the challenges of resumption the development. From the historical trajectories and the analysis of the institutions of professional and technological education in Brazil and Argentina, we seek to perceive the ways and results accomplished in order to establish possible comparisons between the professional and technological education of both countries in the last decade, guiding us with the comparative studies in education field.